Dynamics of Religious Thought in Pesantrens in Indonesia: Between Radicalism, Moderation, and Liberalism - Khoiriyah, Siti; Noor, Aditia Muhammad; Ibrahim, Abdullah Malik (Al Ulya: Jurnal Pendidikan Islam, 2024)
This research aims to track the evolution of thought and religious movements in Islamic boarding schools (pesantren) within the era of globalization. The approach employed in this study is literature review. The findings from this research indicate that radicalism and liberalism within a pesantren are greatly influenced by its leaders, whether they are the owners, kyai (religious leaders), or senior students (santri). If the leaders of a pesantren tend towards radical views, then the pesantren and its students are likely to also hold radical perspectives. Conversely, if the leaders maintain moderate attitudes, the pesantren and its students are inclined towards moderation, and in certain situations and times, may even lean towards liberalism. In the context of globalization, pesantren in Indonesia are no longer entirely dominated by traditional or fundamental-radical groups. New pesantrens established by other Islamic groups have altered the landscape of pesantren, each with its unique identity. This illustrates changes in the face and mindset of pesantren, which have become increasingly diverse over time due to the influence of globalization.